CONSTRUCTION OF CORRELATION MODELS OF OSCILLATORY PROCESSES BY AN ALTERNATIVE METHOD (American Journal of Interdisciplinary Research and Development, 2025)
This article examines economic processes with correlational dependencies that change over time according to a harmonic law, and it also proposes a method for determining the period, phase, and frequency of the oscillations in these processes. The article proposes a method for determining the coefficients A and B in the harmonic function, which was obtained as a result of research.